Clinical Presentation and Laparotomy Findings of Patients With Malignant Adnexal Mass Among Pre-and Postmenopausal Women Attending in Bangabandhu Sheikh Mujib Medical University (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Adnexal malignancies, originating from structures such as the ovaries and fallopian tubes, are a significant health concern, often affecting elderly females. This study aimed to investigate the clinical presentations and laparoscopic findings in patients with malignant adnexal tumors.Materials and methods: An observational cross-sectional study was conducted at the Department of Obstetrics and Gynaecology, Bangabandhu Sheikh Mujib Medical University, Dhaka. Bangladesh, from February 2022 to July 2022. A total of 35 patients meeting the inclusion criteria were enrolled. Epidemiological, demographic and clinical data were collected, including laboratory findings and laparotomy results. Data were analyzed using SPSS-25.  Results: The mean age of participants was 45.11±13.63 years, with 60% over 50. Most patients were multiparous (77.1%) and postmenopausal. Abdominal pain was the most common presenting symptom (80%), followed by anorexia (51.4%) and abdominal distension (40.4%). A significant percentage of patients were underweight (42.9%), anemic (60%), and had edema (8.6%). Laboratory findings revealed elevated CA-125 levels (88.5%) and other tumor markers. Histopathological analysis showed papillary serous cystadenocarcinoma (52.9%) and mucinous cystadenocarcinoma (17.6%) as the most common types.  Conclusion: This study provides clinical insights into the presentation of malignant adnexal masses, highlighting common histopathological types. While limited in size, this study contributes valuable information on the clinical profiles of adnexal malignancies.JCMCTA 2024; 35 (1): 155-160